2022
DOI: 10.3390/ijms23073569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on T2D-Induced MAM Ca2+ Uncoupling and Contractile Dysfunction in an Early Mouse Model of Diabetic HFpEF

Abstract: Diabetic cardiomyopathy (DCM) is a leading complication in type 2 diabetes patients. Recently, we have shown that the reticulum-mitochondria Ca2+ uncoupling is an early and reversible trigger of the cardiac dysfunction in a diet-induced mouse model of DCM. Metformin is a first-line antidiabetic drug with recognized cardioprotective effect in myocardial infarction. Whether metformin could prevent the progression of DCM remains not well understood. We therefore investigated the effect of a chronic 6-week metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Therefore, metformin might be a promising drug for the treatment of DCM via MAM. Maya et al showed that metformin improved blood glucose levels and insulin sensitivity in HFHSD mice; however, it could not prevent the alteration of MAM Ca 2+ coupling in cardiomyocytes and ameliorate the progression of DCM [ 124 ]. These findings further underscore the critical role of MAM Ca 2+ coupling as a potential therapeutic target for DCM and highlight the essential drug specificity of targeting MAM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metformin might be a promising drug for the treatment of DCM via MAM. Maya et al showed that metformin improved blood glucose levels and insulin sensitivity in HFHSD mice; however, it could not prevent the alteration of MAM Ca 2+ coupling in cardiomyocytes and ameliorate the progression of DCM [ 124 ]. These findings further underscore the critical role of MAM Ca 2+ coupling as a potential therapeutic target for DCM and highlight the essential drug specificity of targeting MAM.…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting MAM-related proteins does not necessarily alter the MAM itself. For example, a study by Maya et al showed that although metformin treatment improves blood glucose levels and insulin sensitivity to some extent in diabetic mice, it does not prevent the changes in MAM Ca 2+ coupling in cardiac muscle cells and the resulting heart dysfunction induced by T2D 157 . On the other hand, Wei et al found that activation of transient receptor potential cation channel subfamily V member 1 (TRPV1) by capsaicin alleviated mitochondrial dysfunction caused by high glucose in podocytes and was accompanied by a reduction in MAM formation and decreased Ca 2+ transport from the ER to mitochondria 158 .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between oxidative stress, inflammatory response, and the gut microbiota supported the utilization of ginsenoside Rg1 as a potential treatment for T2D. Metformin was used as a positive control drug, which was the first line of treatment for patients with T2D (Dia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%